Retained Barium in the Appendix Is Difficult to Distinguish from Surgical Remnants following Laparoscopic Surgery. (26th June 2018) - Sato, Masakazu; Koizumi, Minako; Hino, Takahiro; Takahashi, Yu; Nagashima, Natsuki; Itaoka, Nao; Ueshima, Chiharu; Nakata, Maki; Hasumi, Yoko
Abstract : Surgical materials, such as gauze, can be accidentally left inside of patients following surgery. This iatrogenic complication should be avoided and is often prevented by routine X-ray analysis after surgical abdominal procedures. We report a case of retained barium in the appendix that was difficult to distinguish from surgical remnants. A 41-year-old Japanese female was diagnosed with uterine leiomyoma and underwent laparoscopic myomectomy. The postoperative X-ray test showed a cord-like material in the lower right abdomen that was not captured in the preoperative X-ray test two months prior to the operation. Because of this difference, the area was reexamined laparoscopically. After examination, we concluded that the cord-like material in X-ray tests was in fact retained barium in the appendix. Barium can be retained in the appendix for long periods of time, and retained barium in the appendix can be captured radiographically and can mimic the appearance of surgical remnants, appearing as a cord-like material. The knowledge above combined with detailed interviews before surgery could prevent such confusion during interpretation of X-ray tests after surgery.